Penentuan Awal Waktu Sholat Sebagai Syarat Sah Sholat - slamet, Slamet; laili, afrohatul; sururi, endri (Fakta: Forum Aktual Ahwal Al-Syakhsiyah, 2023)
Muslims. Performing prayers on time is an absolute prerequisite for prayers to be considered valid. Determining prayer times is important because based on Islamic teachings, prayer times have been determined and are closely related to the movement of the sun and geographical conditions. Astronomical and geographical factors, such as the sun, latitude and longitude, influence the determination of prayer times. The morning prayer begins before the sun rises, Dhuhr when the sun is at the top of the sky, Asr before the sun sets, Maghrib when the sun sets, and Isha after dusk ends. The suitability of prayer times to seasonal changes is also taken into account in areas that experience significant variations in weather and duration of day and night. Observance of prayer times is an integral part of a Muslim's adherence to religious teachings. Spiritual awareness and devotion to Allah are reflected in efforts to perform prayers at the specified times. It also creates a deep spiritual discipline, strengthening the connection between humans and their creator. Commitment to understanding and adhering to prayer times according to religious guidelines is essential in maintaining a Muslim's obedience. Most Muslims rely on local religious authorities or religious institutions to determine appropriate prayer times according to geographic and astronomical factors. This strengthens Muslims' attachment to religious teachings, making determining prayer times an integral part of their spiritual life.